PENGARUH KINERJA KEUANGAN TERHADAP STABILITAS PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Kasus pada Bank yang Terdaftar di BEI Tahun 2014-2018) - Ketaren, Eka Violeta; Haryanto, Antonius Mulyo (Faculty of Economics and Business Diponegoro University, 2020)
This research aims to examine the effect of bank financial performance on banking stability listed on the Indonesia Stock Exchange. Bank financial performance as measured by Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Operational Expenditures to Operating Income, Non Performing Loans (NPL), and Loan to Deposits Ratio (LDR) as independent variables and dependent variables is Banking Stability using the Z-Score Return on Assets (ROA).This research used secondary data with population consists of 44 commercial banks listed on Indonesia Stock Exchange in the period of 2014-2018. The purposive sampling method used was used in selecting the research sample and 30 conventional commercial banks from the banking sector. This research was conducted based on financial intermediation theory and competition theory using multiple regression analysis..The results of this research indicate that Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL) have a positive significant effect on Return on Assets (ROA). But, Net Interest Margin (NIM) has a negatif significant effect and Operational Expenditures on Operating Income (BOPO) and Loan to Deposits Ratio (LDR) have no negative significant effect on Return on Assets (ROA). This research has implications. The implication of this research is that bank supervisors must have clear regulations and ensure that regulations are designed to reduce risks and avoid defaults so that the profitability of banks increases in Indonesia.